Bronze Sculpture of Mara Vijaya of National Museum, Nepal: A Study of Iconographic Perspective - Dulal, Lok N. (Molung Educational Frontier, 2024)
In Buddhism the images display the story and event of temptation of Mara to disturb and misguide devotion during the process of enlightenment of Siddhartha Gautam. The art which reflects this is called the icon of Mara Vijaya. The legend regarding the story of temptation of evil Mara over the good Sidhhartha Gautam can be found in several Buddhist texts. Due to the iconographic features and themes of the Buddha Jataka stories of temptation of Mara, the bronze sculpture of national museum is considered as an important specimen. The figures of Lord Buddha, demon Mara, his daughters, army troops, Ganesh and other animal’s figures have been sculptured in very attractive ways in this bronze relief. This paper explores the major iconographic features and to examine its importance as the bronze art heritage of Nepal. It employs qualitative approach and primary data and secondary information have been used. Required secondary information has been generated from journals, books and electronic versions of different sources while primary data have been collected by doing field study in national museum with in-depth observation of such relief.